Thomas Hardy, Two on a Tower : vers une redéfinition cosmique de l’appartenance - Laurence Estanove (Cahiers Victoriens et Edouardiens)
In Two on a Tower (1882), Hardy considers the individual’s possibility of belonging to a much larger group than the social community of men, by confronting his astronomer-protagonist with the frightening boundlessness of the cosmos. The discovery of the sublime universe thus creates a new sense of belonging, one that is cosmic, and takes man out of his Christian anthropocentric paradigm, and into the great Darwinian family of the species.